1977
DOI: 10.1113/jphysiol.1977.sp011694
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between the calcium‐dependent effects of cholecystokinin‐pancreaozymin and the bicarbonate‐dependent effects of secretin in exocrine secretion of the rat pancreas.

Abstract: SUMMARY1. Differentiation between the secretary effects of pure natural cholecystokinin-pancreozymin (COK-PZ) and those of synthetic secretin was studied in the isolated pancreas of the rat perfused with a standard solution containing both Ca2+ and HCO3-, a Oa2+-deficient solution, or a HC-G-deficient solution.2. Secretin induced a dose-dependent increase in the flow of pancreatic juice and a slight but definite increase in amylase output which was also dependent upon the dose of secretin.3. The increase in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0
1

Year Published

1979
1979
1993
1993

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 28 publications
3
19
0
1
Order By: Relevance
“…The present experiments have also demonstrated that CCK-PZ hyperpolarizes the pancreatic acinar cell. These results accurately coincided with those obtained in the isolated and perfused rat pancreas (Kanno, 1972(Kanno, , 1975Kanno andSaito 1976, 1978 ;Kanno et al, 1977).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The present experiments have also demonstrated that CCK-PZ hyperpolarizes the pancreatic acinar cell. These results accurately coincided with those obtained in the isolated and perfused rat pancreas (Kanno, 1972(Kanno, , 1975Kanno andSaito 1976, 1978 ;Kanno et al, 1977).…”
Section: Discussionsupporting
confidence: 87%
“…In rat pancreas, it was shown that secretin induced a dose-dependent increase in the flow of pancreatic juice and a slight but definite increase in amylase output which was also dependent upon the dose of secretin (Kanno and Yamamoto, 1977) . In the kitten pancreas, the present experiments have shown that secretin induced a dosedependent increase in the flow but a negligible increase in the pancreatic protein output except for a transient increase which may quite well be due to flushing of the pancreatic protein retained in the ductal lumen.…”
Section: Discussionmentioning
confidence: 98%
“…In recenit years it has become apparent that CCK also stimulates release of a Cl--rich fluid, which is presumiieed to originate from acinar cells and is distinct from the juice secretedl by the pancreatic ducts (24,25). Because both exogenous and endogenous insulin potentiate pancreatic fluidl as well as enzyme secretion, it is likely that insulin acts on a process common to both.…”
Section: Discussionmentioning
confidence: 99%
“…cockroach salivary gland , blowfly salivary gland (Prince & Berridge, 1973), rat parotid gland (Petersen & Pedersen, 1974;Rudich & Butcher, 1976;Petersen, Ueda, Hall & Gray, 1977) and exocrine pancreas (Agent, Case & Scratcherd, 1973;Petersen & Ueda, 1976;Kanno & Yamamoto, 1977;Petersen, 1977 a andLaugier &Petersen, 1980). These have led to the proposal of intracellular calcium-dependent stores of some substance (possibly calcium itself) essential for the response to stimulation.…”
Section: Introductionmentioning
confidence: 99%